2008
DOI: 10.2337/dc07-2323
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Alveolar Microvascular Reserves in Type 2 Diabetes Reflect Systemic Microangiopathy

Abstract: OBJECTIVE -Alveolar microvascular function is moderately impaired in type 1 diabetes, as manifested by restriction of lung volume and diffusing capacity (DL CO ). We examined whether similar impairment develops in type 2 diabetes and defined the physiologic sources of impairment as well as the relationships to glycemia and systemic microangiopathy. RESEARCH DESIGN AND METHODS-A cross-sectional study was conducted at a university-affiliated diabetes treatment center and outpatient diabetes clinic, involving 69 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 23 publications
(31 reference statements)
4
111
1
Order By: Relevance
“…In addition, it has been shown that type 1 diabetic patients treated with a standard twice-daily insulin injection regimen for 6 years presented a significant decrease in FVC in comparison with those who achieved near normoglycaemia treated with subcutaneous insulin infusion [16]. Consequently, diabetic microangiopathy has also been linked with altered lung volume, suggesting a relationship between alveolar and systemic microangiopathy [30]. Our findings reinforce the theory that poorly controlled diabetes is associated with an obstructive pattern of pulmonary abnormalities.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, it has been shown that type 1 diabetic patients treated with a standard twice-daily insulin injection regimen for 6 years presented a significant decrease in FVC in comparison with those who achieved near normoglycaemia treated with subcutaneous insulin infusion [16]. Consequently, diabetic microangiopathy has also been linked with altered lung volume, suggesting a relationship between alveolar and systemic microangiopathy [30]. Our findings reinforce the theory that poorly controlled diabetes is associated with an obstructive pattern of pulmonary abnormalities.…”
Section: Discussionsupporting
confidence: 79%
“…Likewise, restrictive lung disease is not only a result of diabetic microangiopathy [27], but a lower VC is also reported to be an independent predictor of diabetes [12,13]. Lazarus et al [9] found that FVC, FEV1, and maximal mid-expiratory flow rate were predictors of hyperinsulinemia and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pathological microvascular changes may affect gas transfer across the alveolar-capillary membrane (Chance et al, 2008).…”
Section: General Findingsmentioning
confidence: 99%